Effect of Rainfall for the Dynamical Transmission Model of the Dengue Disease in Thailand - Pratchaya Chanprasopchai; Puntani Pongsumpun; I. Ming Tang (My University, 2017)
The SEIR (Susceptible-Exposed-Infected-Recovered) model is used to describe the transmission of dengue virus. The main contribution is determining the role of the rainfall in Thailand in the model. The transmission of dengue disease is assumed to depend on the nature of the rainfall in Thailand. We analyze the dynamic transmission of dengue disease. The stability of the solution of the model is analyzed. It is investigated by using the Routh-Hurwitz criteria. We find two equilibrium states: a disease-free state and an endemic equilibrium state. The basic reproductive number (R0) is obtained, which indicates the stability of each equilibrium state. Numerical results taking into account the rainfall are obtained and they are seen to correspond to the analytical results.
Keywords: Disease Transmission; Mosquito-borne diseases and control